2023
DOI: 10.1001/jamanetworkopen.2023.11004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of 2 Interventions to Increase Breast, Cervical, and Colorectal Cancer Screening Among Women in the Rural US

Abstract: ImportanceWomen living in rural areas have lower rates of breast, cervical, and colorectal cancer screening compared with women living in urban settings.ObjectiveTo assess the comparative effectiveness of (1) a mailed, tailored digital video disc (DVD) intervention; (2) a DVD intervention plus telephonic patient navigation (DVD/PN); and (3) usual care with simultaneously increased adherence to any breast, cervical, and colorectal cancer screening that was not up to date at baseline and to assess cost-effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Several studies conducted by our team and others tested similar interventions that effectively increased CRC screening uptake [ 24 , 26 , 44 , 58 , 79–81 ]. Prior randomized trials of computer-tailored interventions and telephone-based PN conducted by our team showed that these approaches are highly effective at increasing CRC screening [ 24 , 26 , 58 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies conducted by our team and others tested similar interventions that effectively increased CRC screening uptake [ 24 , 26 , 44 , 58 , 79–81 ]. Prior randomized trials of computer-tailored interventions and telephone-based PN conducted by our team showed that these approaches are highly effective at increasing CRC screening [ 24 , 26 , 58 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies conducted by our team and others tested similar interventions that effectively increased CRC screening uptake [ 24 , 26 , 44 , 58 , 79–81 ]. Prior randomized trials of computer-tailored interventions and telephone-based PN conducted by our team showed that these approaches are highly effective at increasing CRC screening [ 24 , 26 , 58 , 80 ]. PN has consistently been shown to be effective at increasing completion of screening colonoscopy, especially among minority and low-income populations [ 40 , 44 , 48–50 , 52 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most interventions that engage the community to improve colorectal cancer outcomes are focused on improving screening uptake in populations who are due for or overdue for screening. We have previously described effective patient navigation methods and multilevel provider and system-level interventions (including use of multimedia and mailed materials) in increasing uptake of colon cancer screening tools (fecal occult blood testing [FOBT], flexible sigmoidoscopy, colonoscopy) in Black patients, 22 with similar interventions on a larger scale and prospective basis showing promise in rural minoritized populations 23,24 . Hispanic and Latino patients represent an important minority group, as despite generally having lower incidence and mortality from colon cancer, uptake of colorectal cancer screening for this population is below that of non-Hispanic Whites and varies widely by place of origin 25…”
Section: Interventions and Strategies Along The Cancer Continuummentioning
confidence: 99%
“…We have previously described effective patient navigation methods and multilevel provider and system-level interventions (including use of multimedia and mailed materials) in increasing uptake of colon cancer screening tools (fecal occult blood testing [FOBT], flexible sigmoidoscopy, colonoscopy) in Black patients, 22 with similar interventions on a larger scale and prospective basis showing promise in rural minoritized populations. 23,24 Hispanic and Latino patients represent an important minority group, as despite generally having lower incidence and mortality from colon cancer, uptake of colorectal cancer screening for this population is below that of non-Hispanic Whites and varies widely by place of origin. 25 Patient navigation, use of small media, and community health worker (CHW)-led interventions have been successfully implemented to improve colorectal cancer screening behaviors in Hispanic and Latino patients.…”
Section: Interventions and Strategies Along The Cancer Continuum Scre...mentioning
confidence: 99%